3D visualization and 3D printing in abnormal gastrointestinal system manifestations of situs ambiguus - Etherton, Dior; Tee, Lisa; Tillett, Carley; Wong, Y.H.; Yeong, C.H.; Sun, Zhonghua (AME Publishing Company, 2020)
Situs ambiguus is a rare congenital condition whereby sufferers have abnormally positioned viscera (1,2). In such cases, it is dangerous to perform traditional diagnostic examinations, such as colonoscopy, thus anatomy is explored through invasive surgeries instead. By reconstructing a patient’s viscera three-dimensionally, it is possible to trace the physical origins of the patient’s symptoms, while eliminating the necessity for invasive surgery. We present a case of situs ambiguus with use of a combination of different approaches including 3D visualizations and patient-specific 3D printing technique to assist clinical diagnosis and patient management. This case highlights the potential value of utilising the latest visualization tools in the diagnostic assessment of complicated pathologies.